Requirement for Pangolin/dTCF in Drosophila Wingless signaling. - Schweizer, L.; Nellen, D.; Basler, K. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
The Wingless (Wg) protein is a secreted glycoprotein involved in intercellular signaling. On activation of the Wg signaling pathway, Armadillo is stabilized, causing target genes to be activated by the transcription factor Pangolin (Pan). This study investigated the roles of Pan in the developing wing of Drosophila by clonal analysis. Three different aspects of wing development were examined: cell proliferation, wing margin specification, and wg self-refinement. Our results indicate that Pan function is critically required for all three of these processes. Consequently, lack of pan causes a severe reduction in the activity of the Wg target genes Distalless and vestigial within their normal domain of expression. Loss of pan function does not, however, lead to a derepression of these genes outside this domain. Thus, although Pan is positively required for the induction of Wg targets in the wing imaginal disk, it does not appear to play a default repressor function in the absence of Wg input. In contrast, lack of zygotic pan function causes a milder phenotype than that caused by the lack of wg function in the embryo. We show that this difference cannot be attributed to maternally provided pan product, indicating that a Pan repressor function usually prevents the expression of embryonic Wg targets. Together, our results suggest that for embryonic patterning the activator as well as repressor forms of Pan play important roles, while for wing development Pan operates primarily in the activator mode.